(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines the translation of profanity, intimate scenes, and sexual lexis in Sidney Sheldon’s political detective novel Windmills of the Gods by comparing the English original with its Russian and Uzbek translations. The study outlines the theoretical foundations of linguistic translation studies, emphasizing the translator’s dual responsibility to maintain both semantic and stylistic equivalence while adhering to the sociocultural norms of the target language. Through comparative analysis, it identifies translation strategies such as euphemization, dysphemization, literal translation, and omission. The findings show that while the Russian translation tends to preserve the expressive and emotional force of the original, the Uzbek translation displays a greater degree of cultural adaptation, often neutralizing taboo or offensive elements. This difference highlights the influence of cultural, moral, and linguistic factors on the translator’s choice and demonstrates the complex interplay between fidelity and acceptability in cross-cultural translation.